2017
DOI: 10.1177/2325967117725031
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sports and Recurrences After Arthroscopic Anterior Shoulder Stabilization in Martial Arts Athletes

Abstract: Background:The high demands to the glenohumeral joint and the violent shoulder blows experienced during martial arts (MA) could compromise return to sports and increase the recurrence rate after arthroscopic stabilization for anterior shoulder instability in these athletes.Purpose:To report the functional outcomes, return to sports, and recurrences in a series of MA athletes with anterior shoulder instability treated with arthroscopic stabilization with suture anchors.Study Design:Case series; Level of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“… 22 , 23 However, in competitive high-risk athletes (such as those included in our study), the results have not been so encouraging. 5 , 6 , 24 , 25 , 26 Among these are collision athletes, those who practice forced overhead sports and athletes with a previous failed Bankart stabilization surgery. 5 , 6 , 7 , 24 , 25 , 26 Trinh et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 22 , 23 However, in competitive high-risk athletes (such as those included in our study), the results have not been so encouraging. 5 , 6 , 24 , 25 , 26 Among these are collision athletes, those who practice forced overhead sports and athletes with a previous failed Bankart stabilization surgery. 5 , 6 , 7 , 24 , 25 , 26 Trinh et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies published in the last decade have shown that in some risk subgroups, the results with Bankart repair are even unfavorable when patients have a glenoid bone deficit of less than 20%. 4 , 5 , 6 , 7 , 8 These risk subgroups mainly include contact and collision athletes, forced overhead athletes, and patients with previous failed Bankart repairs. 4 , 5 , 6 , 7 , 8 The main problem in these high-risk patients is the high recurrence rate, which can vary between 15% and 51%.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 7 (11%) studies 18,24,39,42,70,76,101 used a generic health questionnaire in combination with a diseasespecific PRO tool, whereas 22 (35%) studies § § used a visual analog scale to assess pain in combination with a disease-specific and/or generic health questionnaire. Further, 8 (13%) studies 15,22,37,42,72,73,85,86 recorded the results of a sport-specific questionnaire in combination with a disease-specific and/or generic health questionnaire. No studies included in our review used a PRO tool to assess psychosocial factors.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%